Tourist experience evaluation in a cross-border region - Liberato, Dália (2020)
The development of tourism in cross-border regions has been attracting the interest of several international researchers in this area. This article aims to evaluate the tourist experience in the Eurocity Chaves–Verín region, in particular, to identify the relationships between the characteristics of the trip, the individual profile and the experience perception based on the 4 E's, on the behavioural intentions of tourists, regarding the intention of recommending the destination, through a proposed hypothesis: the length of stay, the tourist resources visited, and the individual profile of the tourist positively influence the perception of the 4E's and the intention to recommend the destination. A total of 166 visitors/tourists were interviewed, 87 in Chaves and 79 in Verín. In the evaluation of the data obtained in Chaves and Verín, for the global model, all the dependent variables are related to the independent variables, statistically significant: the intention to recommend the destination Chaves is superior for those who spend 3 to 5 nights compared to those who spend 5 to 10 nights, and for those who visit the Way of St. James; the intention to recommend the destination Verín is superior for those who visit religious heritage/religious festivals/pilgrimages, and for those who do not visit natural spaces/landscape/nature.